INCIDENCE AND RISK FACTOR OF ACUTE KIDNEY INJURY POST OPEN HEART SURGERY IN PAEDIATRIC PATIENTS - Heriwardito, Aldy; Alatas, Anas; Perdana, Aries; Sutedja, Anasthasia Devina (Bali Journal of Anesthesiology, 2018)
Introduction: Acute Kidney Injury (AKI) was a frequently complication after open heart surgery, especially in paediatric patients < 2 years old and had been related with increased mortality and adverse renal outcomes. This study aimed to know the incidence of AKI post open heart surgery in paediatric patients and its relation with duration of cardiopulmonary bypass (CPB) and patientâs age in Indonesia tertiary national hospital.Methods: This was a cohort retrospective study, using medical record and Cardiac ICU chart data, of 195 paediatric patients who underwent open heart surgery from June 2014 - June 2015 in Integrated Cardiovascular Center Cipto Mangunkusumo hospital. After ethical approval from Research Ethic Committee, data were collected and sorted by inclusion and exclusion criteria. AKI was diagnosed based on RIFLE criteria. Data were analyzed by chi-square and multivariate analysis (SPSS software 22.0 version).Results: Incidence of AKI post open heart surgery in paediatric patients was 36.4%. Duration of CPB > 60 min had a significant correlation with increased incidence of AKI (p 0.043; RR 1.248). Patientâs age â¤ 2 years old also had a significant correlation with increased incidence of AKI (p<0.001; RR 2.431). Multivariate analysis results showed that both duration of CPB > 60 min and patientâs age â¤ 2 years old were significant risk factors of AKI (OR 2.951, OR 5.371).Conclusion: Incidence of AKI post open heart surgery in paediatric patients was 36.4%. Duration of CPB duration > 60 min and patientâs age < 2 years old were significant risk factors of AKI.